Albania : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Use of Fund Resources-Request for an Extended Arrangement. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses a Request from Albania for a Three-Year Arrangement under the Poverty Reduction and Growth Facility (PRGF). This arrangement aims to prepare Albania for graduation from IMF-supported programs. If properly implemented, the policies it embodies will reduce vulnerabilities, enhance growth potential, strengthen government solvency, and protect priority spending. These policies will also contribute to improved governance-a precondition for attracting the high-quality investment needed to address the structural imbalances in the external accounts and to ensure the continuation of strong growth. Remaining vulnerabilities in the financial system are also addressed.